HISTORI VARIABILITAS KANDUNGAN PANAS LAUT DI PERAIRAN INDONESIA - Dwi Sasongko, Romanu
The total heat that can be stored in the ocean is called the ocean heat content. The heat stored in the ocean has an important role in regulating the climatic conditions on earth. Ocean heat content in Indonesian seas is calculated using vertical and horizontal monthly temperature data based on Met Office Hadley Observation "EN 4.1.1” with resolution 10 x 10 from the period 1901- 2015. Ocean heat content is calculated in the depth of 0-100 m, 0-300 m, and also the total depth of Indonesian Seas. There was an increase in the ocean heat content value at a depth of 0-100 m and at a depth of 0-300 m, the heat content value has reached 2x1014 J and 2x1013 J, the ocean heat content at total depth decrease reached -2x1014 J. The largest change of ocean heat content in Indonesia occurs at a depth of 100-300 m reaching an average value of 13 J and a change in heat content below 1000 m is reduced by 5 J in each depth. Pacific Decadal Oscillation (PDO) positive phase causes the decrease of ocean heat content averaged equal to -1,74 x 1017 J in 1901-2015, otherwise in negative phase cause increase of sea heat content averaged equal to 2,48 x 1017 J in same periode. Meanwhile in 1926-1940 positive phase of PDO did not cause decrease ocean heat content value.